Three-year post-stroke outcomes in urban North-western Tanzania - Ngimbwa, Joshua; Nchasi, Goodluck; Paul, Innocent Kitandu; Kasala, Anna; Mwamba, Lilian Andrew; Berling, Sospeter; Basinda, Matilda K.; Xavier, Gladness; Andrew, Benjamin; Mawazo, Akili; Lucas, Dorice; Mahawish, Karim; et al. (Frontiers in Stroke, 2025)
Backgroundstroke is one of the leading causes of death and disability globally. Despite advancements in acute stroke care, long-term outcomes have not been extensively studied in Tanzania. This study aimed to investigate the long-term post-stroke outcomes among adults admitted with stroke to a large tertiary hospital in northwestern Tanzania.Methodsadults (≥18 years) with stroke who were enrolled in the Lake Zone Stroke Registry Study (LZSS) at Bugando Medical Center between March 2020 and October 2021 were prospectively followed up until October 2024. Stroke diagnosis and classification were confirmed using brain imaging, and baseline stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS). Data on case fatality were collected using the modified Rankin Scale along with information on secondary stroke prevention. The Kaplan–Meier analysis was used to describe survival, and the Cox regression model was used to examine independent factors associated with fatality.Resultsthe study included 301 adults, with a mean age of 65.5 ± 14 years, of whom 51% (153/301) were female and 68% (205/301) had ischemic strokes. Case fatality rates were 42.9% (98/228) at 1 year, 75.9% (173/228) at 2 years, and 96.5% (220/228) at 3 years. Independent factors associated with fatality were severe stroke (adjusted hazard ratio (aHR) 7.9, 95% CI [2.3, 27.4], p = 0.001), moderate to severe stroke (aHR 4.6, 95% CI [1.3, 16.1], p = 0.017), a lack of health insurance coverage (aHR 3.7, 95% CI [1.9, 6.8], p < 0.001), and previous stroke (aHR 3.3, 95% CI [1.3, 8.3], p = 0.01). Attendance rates of follow-up clinics and physiotherapy among survivors were 28.6% (86/301) and 8.6% (26/301), respectively. Among stroke survivors with hypertension and diabetes, 32% (83/257) and 41% (20/49) were adherent to antihypertensive and diabetic medications, respectively.Conclusionthis study highlights the high long-term case fatality rates among adults with stroke in northwestern Tanzania, with stroke severity, a lack of health insurance, and previous strokes being key factors associated with fatality. Low attendance rates at follow-up clinics and poor adherence to medications among survivors of stroke with hypertension and diabetes underline the importance of strengthening post-stroke care systems, including health insurance coverage, to improve survival and quality of life.